Step 1

Given

\(\displaystyle{3}{x}^{{2}}+{4}{x}-{4}\)

Step 2 By factorization

\(\displaystyle{3}{x}^{{2}}+{6}{x}-{2}{x}-{4}\)

3x(x+2)-2(x+2)

(x+2)(3x-2)=0

x+2=0, 3x-2=0

x=-2, 3x=2

\(\displaystyle{x}=\frac{{2}}{{3}}\)

\(\displaystyle\therefore\) Zeroes are \(\displaystyle\frac{{2}}{{3}}\) and -2

Given

\(\displaystyle{3}{x}^{{2}}+{4}{x}-{4}\)

Step 2 By factorization

\(\displaystyle{3}{x}^{{2}}+{6}{x}-{2}{x}-{4}\)

3x(x+2)-2(x+2)

(x+2)(3x-2)=0

x+2=0, 3x-2=0

x=-2, 3x=2

\(\displaystyle{x}=\frac{{2}}{{3}}\)

\(\displaystyle\therefore\) Zeroes are \(\displaystyle\frac{{2}}{{3}}\) and -2